Dynamic Advanced Analysis and Maintenance Strategies for Airport Pavements: A Comprehensive Literature Review - Mustafa I. Ahmed; Alaa H. Abed (مجلة النهرين للعلوم الهندسية, 2025)
Flexible and rigid pavements are commonly built for airport pavements to support the moving loads of aircraft during the pavement design life. Airport pavements represent a cornerstone of the aviation world. Their condition profoundly impacts safety, operational efficiency, airport capacity, and financial well-being. These meticulously engineered surfaces must withstand the immense stresses generated by aircraft during takeoff, landing, and taxiing. At the planning stage, the pavement structure, materials, aircraft loads, environmental conditions, and pavement damage models should be evaluated. Comparing with road pavement design, airport pavement structural design is unique in terms of the traffic loads supported by pavements with high load magnitude, significant tire pressure, and dynamic traffic conditions. Over time, deterioration stemming from environmental exposure, aircraft loading, and other factors becomes inevitable. This study aims to explore the various factors influencing airport pavement performance, review the existing methodologies for pavement design and maintenance, and propose enhancements to current practices to ensure long-term durability and safety of airport pavements. This study aims to explore the various factors influencing airport pavement performance, review the existing methodologies for pavement design and maintenance, and propose enhancements to current practices to ensure long-term durability and safety of airport pavements.